Efeitos auditivos da toxoplasmose adquirida experimental em camundongos BALB/c - Bianca Cristina Eugênio (2016)
Introduction: acquired toxoplasmosis is a parasitic infection transmitted by Toxoplasma gondii. Although this infection is a possible risk factor for hypoacusis, there are few reports in the literature on the pathogeny of acquired toxoplasmosis in the auditory system. Objective: to verify and characterize hearing effects caused by acquired toxoplasmosis in BALB/c mice. Material and methods: experimental study in female BALB/c mice. In a first moment, we researched the cochlear auditory effects caused by ME-49 strain of T. gondii. Distortion Product Otoacoustic Emissions examination was recorded, in the frequencies of 08 and 10 kHz, with Audx Plus (Biologic©) ecquipment. Later, the effects on peripheral and central hearing caused by brazilian strain TgCTBr5 were investigated. At this stage, it was used the OtoPhyLab® (RT Conception), the specific equipment for recording auditory responses in animal experimentation. Distortion Product Otoacoustic Emissions were surveyed in the frequencies of 08, 12, 16, 24 and 32 kHz. Auditory Brainstem Responses in the frequencies of 10, 16, 24 e 32 kHz were also performed. In both steps, after the end of the experiment, all mice were euthanized and Toxoplasma gondii IgG antibodies were researched by Elisa. Cochleas were removed for optical and microscopic analyses. Brain and brainstem were taken out for histopathological study. The statistical analysis was carried out in SPSS software, version 19, and the significance level adopted was 5% (p 0.05). It was made a comparison by intra subject responses and the stage of infection and also an inter subject comparison by the experimental groups and the corresponding control groups. Microscopic and histopathological analyses were descriptive. Results: the ME-49 strain did not cause significant cochlear changes in the frequencies of 08 and 10 kHz. The TgCTBr5 strain did not damage the peripheral and central auditory systems. The Elisa confirmed the success of infection, both for ME-49 strain and TgCTBr5 strain. Electron microscopy of the cochlea did not show changes in external ciliated cells for both control groups as to the experimental groups infected by TgCTBr5 strain. Toxoplasma gondii was not observed in the cochlea, brain and brainstem by histopathological analysis. Mice infected in the acute phase disclosed subtle increasing of meninges, and the ones infected in the chronic phase presented lymphocytes in the central nervous system. Conclusion: the cochlear region corresponding to 08 and 10 kHz frequencies was not impaired by infection with the ME-49 strain of Toxoplasma gondii. The brazilian strain TgCTBr5 did not affect the peripheral and central auditory systems of BALB/c mice.